Deep trade policy options for Armenia: The importance of trade facilitation, services and standards liberalization - Jesper Jensen; David G. Tarr (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
In this paper the authors develop an innovative 21 sector computable general equilibrium model of Armenia to assess the impact on Armenia of a Deep and Comprehensive Free Trade Agreement (DCFTA) with the EU, as well as further regional or multilateral trade policy commitments. They find that a DCFTA with the EU will likely result in substantial gains to Armenia, but they show that the gains derive from the deep aspects of the agreement. In order of importance, the sources of the gains are: (i) trade facilitation and reduction in border costs; (ii) services liberalization; and (iii) standards harmonization. A shallow agreement with the EU that focuses only on preferential tariff liberalization in goods will likely lead to small losses to Armenia primarily due to a loss of productivity from lost varieties of technologies from the Rest of the World region in manufactured products. Additional gains can be expected in the long run from an improvement in the investment climate. The authors estimate only small gains from a services agreement with the CIS countries, but significant gains from expanding services liberalization multilaterally.
Keywords: C68; F12; F13; F14; F15; F17; L16; 330; trade facilitation; services liberalization; standards harmonization; preferential liberalization; multinationals; monopolistic competition; foreign direct investment; endogenous productivity effects; Außenhandelsliberalisierung; Freihandelszone; Wirkungsanalyse; Außenhandelseffekt; Produktivität; Armenien; EU-Staaten; GUS-Staaten